BEYOND THE HALAL SYMBOL: HOW HALAL CERTIFICATION AND PRODUCT QUALITY JOINTLY DRIVE MUSLIM CONSUMER SATISFACTION IN THE SOCIAL MEDIA SKINCARE MARKET - Dewi Masita; Dwi Wardah Akmaliah (IZZI: Jurnal Ekonomi Islam, 2026)
The rapid expansion of the halal cosmetics market, fueled by social media virality, has intensified academic interest in understanding the determinants of Muslim consumer satisfaction in non-food product categories. This study investigates the dual influence of halal certification (X₁) and product quality (X₂) on Muslim consumer satisfaction in the skincare segment (Y), using a sample of 50 respondents recruited from the researcher's 2,300 Instagram followers. Employing a quantitative explanatory design, data were collected via a structured online questionnaire and analyzed using Pearson Product Moment correlation and multiple linear regression. Results confirm that halal certification exerts a statistically significant positive influence on consumer satisfaction (β = 0.412, p < 0.001), while product quality demonstrates an even stronger independent effect (β = 0.537, p < 0.001). Critically, the simultaneous inclusion of both predictors yields a substantially elevated coefficient of determination (R² = 0.684), indicating a synergistic rather than merely additive relationship. These findings challenge the assumption that halal labeling alone is sufficient to ensure satisfaction and provide empirical validation for the Islamic concept of tayyib goodsproducts that are simultaneously religiously permissible and functionally excellent. The study offers evidence-based implications for skincare manufacturers, Indonesia's Halal Product Guarantee Agency (BPJPH), and digital Islamic marketing practitioners navigating the post-mandatory-certification landscape.